Existence of positive solutions for the boundary value problem of a nonlinear fractional differential equation (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, we deal with the following nonlinear fractional boundary value problem                             Dao+u(t) +f(t, u(t))= 0,0 < t < 1,4 < Î±